Yunvjian decoction attenuates lipopolysaccharide-induced acute lung injury by inhibiting NF-κB/NLRP3 pathway and pyroptosis - Zhang, Fanxuan; Wang, Fang; Zhao, Lisha; Wang, Leqian; Li, Wenjing; Huang, Feihua; Wang, Nani (Frontiers in Pharmacology, 2025)
IntroductionYunvjian (YNJ) decoction, a classic traditional Chinese medicine prescription for inflammatory diseases, has demonstrated good therapeutic effects in the clinical treatment of pneumonia. The aim of this study was to clarify the effective ingredients and mechanism of action of YNJ on lipopolysaccharide (LPS)-induced acute lung injury (ALI).MethodsThe effects of YNJ were evaluated in a mouse model of LPS-induced ALI and in LPS-treated MLE-12 murine lung epithelial cells and RAW264.7 macrophages in vitro. The mechanism of action of YNJ on these model systems was studied using RNA sequencing, immunohistochemical analysis, immunoblotting, immunofluorescence, ELISA, and polymerase chain reaction assays. Ultra-high performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry was applied to identify the absorbed components of YNJ.ResultsYNJ attenuated pulmonary damage in LPS-treated mice, as evidenced by reduced protein content in bronchoalveolar lavage fluid, decreased lung wet/dry weight ratio, and improved respiratory function. Analysis of pneumonia-related lung injury samples from patients in the Gene Expression Omnibus dataset GSE40012 indicated that NOD-like receptor protein 3 (NLRP3)-mediated pyroptosis was a primary mechanism in ALI. YNJ reduced the phosphorylation of nuclear factor-kappa B (NF-κB) and decreased the expression levels of lung NLRP3, apoptosis-associated speck-like protein containing a CARD (ASC), cleaved caspase-1, and interleukin-1β levels (IL-1β) in vivo. Administration of YNJ-containing mouse serum increased cell viability and decreased malondialdehyde and reactive oxidative species contents in LPS-stimulated MLE-12 cells. YNJ-containing serum also decreased the secretion of tumor necrosis factor-α, IL-6, and IL-1β in LPS-stimulated RAW264.7 macrophages, and promoted macrophage polarization toward an M2 phenotype. A total of 23 absorbed components were identified in YNJ-containing serum. Among those, network analysis and in vitro experiments indicated that diosgenin, timosaponin BII, and mangiferin are anti-inflammatory active substances.ConclusionYNJ attenuates LPS-induced ALI in mice by inhibiting pyroptosis of lung epithelial cells and macrophages via suppression of the NF-κB/NLRP3 pathway. Our findings provide novel insights into the therapeutic effects of YNJ on ALI.